تأثير أنواع مختلفة من المحسنات العضوية في بعض الخواص الفيزيائية والإنتاجية للقمح في التربة الطينية ضمن معاملات ري مختلفة - بلدية, رياض; زحلان, رهام (Latakia University Journal -Biological Sciences Series, 2019)
أجريت تجربة حقلية خلال الموسمين الزراعيين 2009/2008, و2010/2009 في مركز حوط للبحوث الزراعية في محافظة السويداء. تضمنت الدراسة ثلاث معاملات تحسين عضوي؛ باستخدام ثلاثة أنواع مختلفة من المحسنات العضوية (كومبوست قمامة المدن - حمأة الصرف الصحي - السماد البلدي), إضافة إلى معاملة الشاهد, ومعاملتي ري (70% - 100%) من السعة الحقلية, وبثلاثة مكررات لكل معاملة؛ لمعرفة تأثيرها في بعض الخواص الفيزيائية للتربة الطينية, وإنتاجية القمح/ شام3/. بينت النتائج أن كومبوست قمامة المدن كان الأفضل في تحسين الخواص المدروسة؛ إذ خفض الكثافة الظاهرية للتربة بنسبة (28-25)% في المعاملة (100% ري), و(28-32)% في المعاملة ( 70%ري) في سنتي الدراسة على التوالي, كما خفض الكثافة الحقيقة للتربة, وزاد مساميتها الكلية, ومحتواها من المادة العضوية, ورفع قدرتها على الاحتفاظ بالرطوبة بنسبة (21-15)% في المعاملة (100%ري), وبنسبة (18-16)% في المعاملة (70% ري) في سنتي الدراسة على التوالي. كما خفض الكمية المستهلكة من المياه في الري بمعدل (37-40)% في المعاملة (100% ري), وبمعدل (37-31)% في المعاملة ( 70%ري) في سنتي الدراسة على التوالي. ويتلوه في تأثيره السماد البلدي بفروق ظاهرية فقط في أغلب المؤشرات المدروسة. على حين كانت معاملة حمأة الصرف الصحي الفضلى من حيث الإنتاجية المحققة لنبات القمح؛ بزيادة بلغت (29) % قياساً بالشاهد للمعاملة 100% في سنتي الدراسة, وكانت (33-31)% للمعاملة 70% لسنتي الدراسة على التوالي. وهذا يوضح الأثر الإيجابي لعملية التحسين العضوي للتربة باستخدام بعض المخلفات المعاد تدويرها. A Field experiment was carried out in Hout center for research / in Swaida / over two growth seasons 2008/2009 – 2009/2010. The study included three treatments using three different kinds of organic amendments ( compost of solid waste – sewage sludge – municipal manure ) and two treatments of irrigation (100-70 )% of field capacity with three replicates to measure their effect on some physical properties of clay soil and the productivity of wheat / Sham 3/. The results have shown that compost of solid waste was the best in improving the studied properties. It reduced the soil bulk density of( 25-28)% in (100%) treatment and (32-28)% in (70%) treatment for the two years respectively. It also reduced the soil real density, increased the total porosity and its content of organic matter, and increased its ability to keep water with percentage of (15-20)% in(100%) and of (16-18)% in(70%) in the two years respectively. It also reduced the amount of water used in irrigation in average of(40-37)% in (100%) and (31-37)% in (70%) in the two years respectively. And it followed by the municipal manure with superficial differences in most of the studying parameters. Whereas the treatment of sewage sludge was the best treatment in increasing the achievement productivity of wheat plants which reached (29% ) compared with the control in 100% treatment in the two years , and it was (31-33%) in %70 treatment for the two years respectively.And that shows the positive effect of processing of organic amendments of soil by using some recycled wastes.